Unintended Consequences of Tele Health and their Possible Solutions - Gogia, S. B.; Maeder, A.; Mars, M.; Hartvigsen, G.; Basu, A.; Abbott, P. (Yearbook of Medical Informatics, 2016)
Objectives: Assess unforeseen consequences of Telehealth and suggest solutionsMethods: An outline was created collecting all possible ill effects classified into Clinical considerations, Administrative concerns including interpersonal relations, Technical issues, Legal / Ethical concerns and Miscellaneous. Each topic was assigned to a particular WG member to lead, gather opinion and review existing literature.Results and Conclusion: A wide array of problems have been described. Except for technical issues, literature on this topic is scant, so this article is based more on personal experience and data collected from surveys. Much can be done to prevent such problems, such as a need for standardization with related clinical studies for devices as well as processes used for telehealth is underlined, besides evaluation of outcomes of projects undertaken.
Keywords: Telehealth; Telemedicine; eHealth; Tele-monitoring